G333(P) Serum biomarkers, but not dual-energy x-ray absorptiometry (DXA), predict bone mineral density in children with chronic kidney disease. (25th October 2020) - Lalayiannis, AD; Crabtree, NJ; Askiti, V; Mitsioni, A; Fewtrell, M; Kaur, A; Milford, DV; Shroff, R
Abstract : Introduction: Currently available biomarkers and Dual-energy X-ray Absorptiometry (DXA) are thought to be poor predictors of bone mineral density (BMD). The 2017 KDIGO guidelines on CKD-MBD propose using DXA if it will affect patient management. We set out to determine the clinical utility of DXA and routine clinical biomarkers by comparing them with tibial cortical BMD measured by peripheral Quantitative Computed Tomography (pQCT), which clearly defines cortical and trabecular compartments and predicts future fracture risk. Methods: We performed a prospective multi-centre cross-sectional study in 97 children (5–19 years) with CKD stages 4–5 and on dialysis. Children underwent hip and lumbar spine DXA and tibial pQCT. All DXA and pQCT data were expressed as age corrected Z-scores, and lumbar spine DXA was additionally corrected for height (BMAD Z-score). Imaging findings were correlated with routine serum biomarkers. Results: Hip Z-score and lumbar spine BMAD Z-scores correlated significantly with each other (p<0.001). Hip Z-scores and lumbar spine BMAD Z-scores showed a strong correlation with tibial trabecular BMD (p<0.001), whereas they did not show any correlation with tibial cortical BMD. Neither the hip nor the lumbar spine measures correlated with any biomarkers. PTH showed a positive correlation with tibial trabecular BMD (p=0.024) and a negative correlation with cortical BMD (p<0.001). Tibial cortical BMD was also associated with alkaline phosphatase (p=0.014) and total calcium (p=0.019). On multivariable linear regression analysis the significant and independent predictors of tibial cortical BMD were PTH (β-0.355, p<0.001), alkaline phosphatase (β-0.238, p=0.011) and serum calcium (β 0.184, p=0.052), which together predicted 26% of variability in tibial cortical pQCT. Conclusions: Routinely used biomarkers- calcium, alkaline phosphatase and PTH- when used together are weak to moderate predictors of BMD. No associations were seen with hip or lumbar spine DXA. DXA is not a clinically useful tool and should not be performed routinely.